SPIRITUAL HEALTH SANCTUARIES: HOW RELIGIOUS HOSPITALS ARE MEETING MODERN NEEDS - Redford, James Michael; Kendrick, Anna Louise (International Research Journal Diagnostics, 2024)
In 2021, health expenditures in the United States soared to an astounding $4.3 trillion, equivalent to 18.3% of the Gross Domestic Product (GDP). A significant portion of these expenses, 19%, was attributed to hospital inpatient services. This substantial financial burden has implications for religious hospitals, which often serve as safety net providers, grappling with both organizational and environmental challenges due to the volume of charity care they deliver. Consequently, religious hospitals are compelled to enhance operational efficiency and foster coordination between inpatient and outpatient facilities to meet the evolving demands of healthcare. As state and federal governments contend with mounting financial pressures, religious hospitals confront the prospect of reduced payments from Medicare and Medicaid. The implementation of the CMS Value-Based Purchasing program, commencing in 2017, introduced a 2% reduction in hospitals' base payments, withholding a staggering $1.8 billion. This withheld amount was subsequently distributed to hospitals with the highest quality scores, further emphasizing the need for religious hospitals to refine their operations in order to maintain competitiveness in the dynamic healthcare landscape.